Numerical Analysis of The Wire-Meshed Net Anchoraged - Riski Purwana Putra; Ali Limam; Data Iranata (JEECS (Journal of Electrical Engineering and Computer Sciences), 2021)
The rockfall hazard in areas such as mountainous regions, quarries and mines needs to be well managed. This is essential in order to avoid fatalities, damage to infrastructure and production losses. Preventing all rockfall events is almost impossible, but the installation of rockfall protection systems is a common and effective way to control the hazard. The installation of wire-meshed net anchored is a possible solution to prevent slippage of landslide of the surface layers. This paper will be focused on the study of numerical modeling, using finite element analysis software, ABAQUS, of double-twisted hexagonal wire-meshed net anchoraged which has been developed by the French-based company, GTS. The objective is to analyze several configurations and performances of wire-meshed nets, cables. As final result, we will comparing between the experiment and numerical modeling analysis.